Governing Risk for Project Performance: A Mechanism ‎Based Systematic Review of Cost Overruns and Schedule ‎Delays in Construction - Ramadhan, Jatiaryo Sidiq; Irawan, Agustinus Purna; Taba, Muhammad Idrus (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Cost overruns and schedule delays continue to challenge construction projects worldwide, ‎yet existing research has predominantly focused on identifying risk factors rather than ‎explaining how those risks translate into performance outcomes. This study adopts a ‎mechanism-oriented perspective to examine the managerial and governance systems that ‎mediate the relationship between project risk exposure and cost and schedule performance. ‎A Systematic Literature Review (SLR) was conducted and integrated with bibliometric ‎keyword co-occurrence analysis using VOSviewer to synthesize and map the intellectual ‎structure of the field. Fourteen studies meeting mechanism-based inclusion criteria were ‎analyzed. The results indicate that project performance deterioration is not a direct ‎consequence of risk occurrence alone, but is shaped by interacting governance mechanisms. ‎Risk management emerges as the central coordinating system, financial governance ‎functions as a stabilizing buffer that supports operational continuity, and project control ‎systems serve as the execution-level interface translating governance strategies into ‎performance monitoring and corrective action. Bibliometric mapping further reveals a shift ‎in the literature from problem-oriented discussions of cost overruns toward ‎governance-based performance regulation. These findings support a mechanism-based ‎understanding of construction project performance, where cost and schedule outcomes are ‎governance-dependent rather than purely risk-driven. Methodologically, the study ‎demonstrates the value of combining systematic review rigor with bibliometric mapping to ‎uncover structural knowledge patterns. Practically, the results highlight the importance of ‎strengthening integrated governance systems—not only improving risk identification—to ‎enhance construction project performance.‎